Establishing a multicenter, preclinical consortium in resuscitation: A pilot experimental trial evaluating epinephrine in cardiac arrest. (June 2022) - Lin, Steve; Ramadeen, Andrew; Sundermann, Matthew L.; Dorian, Paul; Fink, Sarah; Halperin, Henry R.; Kiss, Alex; Koller, Allison C.; Kudenchuk, Peter J.; McCracken, Brendan M.; Mohindra, Rohit; Morrison, Laurie J.; et al.
Abstract: Background: Large animal studies are an important step in the translation pathway, but single laboratory experiments do not replicate the variability in patient populations. Our objective was to demonstrate the feasibility of performing a multicenter, preclinical, randomized, double-blinded, placebo-controlled cardiac arrest trial. We evaluated the effect of epinephrine on coronary perfusion pressure (CPP) as previous single laboratory studies have reported mixed results. Methods: Forty-five swine from 5 different laboratories (Ann Arbor, MI; Baltimore, MD; Los Angeles, CA; Pittsburgh, PA; Toronto, ON) using a standard treatment protocol. Ventricular fibrillation was induced and left untreated for 6 min before starting continuous cardiopulmonary resuscitation (CPR). After 2 min of CPR, 9 animals from each lab were randomized to 1 of 3 interventions given over 12 minutes: (1) Continuous IV epinephrine infusion (0.00375 mg/kg/min) with placebo IV normal saline (NS) boluses every 4 min, (2) Continuous placebo IV NS infusion with IV epinephrine boluses (0.015 mg/kg) every 4 min or (3) Placebo IV NS for both infusion and boluses. The primary outcome was mean CPP during the 12 mins of drug therapy. Results: There were no significant differences in mean CPP between the three groups: 14.4 ± 6.8 mmHg (epinephrine Infusion), 16.9 ± 5.9 mmHg (epinephrine bolus), and 14.4 ± 5.5 mmHg (placebo) ( p  = NS). Sensitivity analysis demonstrated inter-laboratory variability in the magnitude of the treatment effect ( p  = 0.004). Conclusion: This study demonstrated the feasibility of performing a multicenter, preclinical, randomized, double-blinded cardiac arrest trials. Standard dose epinephrine by bolus or continuous infusion did not increase coronary perfusion pressure during CPR when compared to placebo.